2013
DOI: 10.1016/j.nano.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Volatile fingerprints of cancer specific genetic mutations

Abstract: We report on a new concept for profiling genetic mutations of (lung) cancer cells, based on the detection of patterns of volatile organic compounds (VOCs) emitted from cell membranes, using an array of nanomaterial-based sensors. In this in-vitro pilot study we have derived a volatile fingerprint assay for representative genetic mutations in cancer cells that are known to be associated with targeted cancer therapy. Five VOCs were associated with the studied oncogenes, using complementary chemical analysis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 44 publications
8
114
0
3
Order By: Relevance
“…Volatile organic compounds (VOCs) have been found in breath, blood [1], headspace of cancer cells [2][3][4][5][6][7][8][9][10], and in headspace of resected cancer tissues [11]. Exhaled breath, which may change its chemical signature depending on the physiological or pathophysiological state of disease [12][13][14][15][16][17][18][19][20][21][22][23][24], is considered as one of the most fascinating body fluids/sources.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) have been found in breath, blood [1], headspace of cancer cells [2][3][4][5][6][7][8][9][10], and in headspace of resected cancer tissues [11]. Exhaled breath, which may change its chemical signature depending on the physiological or pathophysiological state of disease [12][13][14][15][16][17][18][19][20][21][22][23][24], is considered as one of the most fascinating body fluids/sources.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Peled et al reported that 5 VOCs in the headspace of lung cancer cell lines with 3 different genetic mutations and corresponding wild-type cell lines are different from each other. At last, a good classification (with 84%-96% accuracy) among them was reached by using GNP sensors (Peled et al, 2013). …”
Section: E-nose Based On Gold Nanoparticle Sensorsmentioning
confidence: 95%
“…Most recently, Peled et al reported a study on VOCs in the headspace of lung cancer cells with different genetic mutations, in which 5 VOCs were found to be related to specific mutations of lung cancer cells (Peled et al, 2013).…”
Section: Studies On Vocs In Headspace Of Lung Cancer Cell Linesmentioning
confidence: 99%
“…[1][2][3][4][5] These arrays could meet the growing demand for rapid and flexible online detection of a wide range of chemical and biological agents in different branches of industry, homeland security, 5,6 environmental monitoring, 5,7,8 and medical diagnostics [1][2][3][4][5][9][10][11][12][13][14][15][16][17][18][19][20] . Combined with statistical algorithms, these sensor arrays can provide convenient bionics of the mammalian olfactory system for identifying complex gas samples, without the necessity of identifying their separate ingredients.…”
Section: Introductionmentioning
confidence: 99%